Risk factors for the recurrence of cervical cancer using MR-based T1 mapping: A pilot study - Liu, Jie; Li, Shujian; Cao, Qinchen; Zhang, Yong; Nickel, Marcel Dominik; Wu, Yanglei; Zhu, Jinxia; Cheng, Jingliang (Frontiers in Oncology, 2023)
Quantitative T1 mapping helps monitor the progression and prognosis of glioblastoma and hepatocellular carcinoma, respectively. However, although the use of T1 mapping is increasing in tumor studies, the correlation between the T1 relaxation time and the prognosis of patients with cervical cancer (CC) has not been investigated. This study aimed to identify risk factors for recurrence in patients with CC through quantitative T1 mapping. A cohort of 107 patients histopathologically diagnosed with CC at our institution between May 2018 and April 2021 was categorized into surgical and non-surgical groups. Patients in each group were further divided into recurrence and non-recurrence subgroups depending on whether they showed recurrence or metastasis within 3 years of treatment. The longitudinal relaxation time (native T1) and apparent diffusion coefficient (ADC) value of the tumor were calculated. The differences between native T1 and ADC values of the recurrence and non-recurrence subgroups were analyzed, and receiver operating characteristic (ROC) curves were drawn for parameters with statistical differences. Logistic regression was performed for analysis of significant factors affecting CC recurrence. Recurrence-free survival rates were estimated by Kaplan–Meier analysis and compared using the log-rank test. Thirteen and 10 patients in the surgical and non-surgical groups, respectively, showed recurrence after treatment. There were significant differences in native T1 values between the recurrence and non-recurrence subgroups in the surgical and non-surgical groups (P<0.05); however, there was no difference in ADC values (P>0.05). The areas under the ROC curve of native T1 values for discriminating recurrence of CC after surgical and non-surgical treatment were 0.742 and 0.780, respectively. Logistic regression analysis indicated that native T1 values were risk factors for tumor recurrence in the surgical and non-surgical groups (P = 0.004 and 0.040, respectively). Compared with cut-offs, recurrence-free survival curves of patients with higher native T1 values of the two groups were significantly different from those with lower ones (P = 0.000 and 0.016, respectively). Quantitative T1 mapping could help identify CC patients with a high risk of recurrence, supplementing information on tumor prognosis other than clinicopathological features and providing the basis for individualized treatment and follow-up schemes.